Radioactivity distribution and concomitant hazards evaluation of industrial zones soils from Chattogram, Bangladesh: A multivariate statistical analysis - M.M. Mahfuz Siraz; Shahidul Islam; Afroza Shelley; Mohammad Shafiqul Alam; Araf Mahmud; Md. Bazlar Rashid; Mayeen Uddin Khandaker; Selina Yeasmin; M. Safiur Rahman (PLoS ONE, 2025)
Soil can pose significant radiation hazard in areas with elevated radioactivity levels from geological or anthropogenic sources, potentially contributing to human exposure through the food chain and atmosphere. However, industrial activities can alter radionuclides distribution by releasing residues or effluents, leading to their accumulation in the environment. In general, soil provides clear insights into geological characteristics and heavy metal exploration, in addition to assessing the risks of radiation exposure. This study investigates the distribution of NORMs and assesses radiological hazards in twenty soil samples collected from two major industrial zones in the Chattogram City of Bangladesh: the Bayazid Industrial Area and the Kalurghat Heavy Industry Area. The activity concentrations of 226Ra, 232Th, and 40K in the analyzed soil samples range from 8 ± 1–18 ± 1, 15 ± 1–35 ± 3, and 192 ± 17–420 ± 35 Bq/kg, respectively, remaining below the global average for soil. The radiological hazard indices indicate negligible health risks to the public or environment, suggesting that the industrial activities are not releasing any radiotoxic elements in the surrounding environment. Statistical analysis identified 40K and 232Th as the primary contributors to radiological hazards, supported by strong correlations and significant principal component loadings. Additionally, this study provides baseline data for monitoring environmental radioactivity levels, particularly in light of the upcoming commissioning of the Rooppur Nuclear Power Plant in 2025.